2008
DOI: 10.1016/s1808-8694(15)31096-x
|View full text |Cite
|
Sign up to set email alerts
|

Otoscopic and tympanometric findings in infants with cleft lip and palate

Abstract: female and male infants with cleft lip and palate did not differ as far as otoscopic and tympanometry findings are concerned. All types of tympanometric curves were present, and types A and B were the most frequent ones. Ear drum opacification was the most frequent otoscopic finding. Pneumatic otoscopy identified a larger number of alterations when compared to conventional tympanometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…This is contradictory to prior research. Studies in which otolaryngologic maintenance care and PE tube placement reported that complete and bilateral clefts require additional PE tube placements secondary to persistent effusions and lesser hearing improvement over time, respectively (Ahn et al, 2012; Feniman et al, 2008; Handžic-Cuk et al, 1996). Finally, most studies have identified no gender predilection for later increased risk for otologic disease, with a minority reporting an increased risk in males (Ahn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contradictory to prior research. Studies in which otolaryngologic maintenance care and PE tube placement reported that complete and bilateral clefts require additional PE tube placements secondary to persistent effusions and lesser hearing improvement over time, respectively (Ahn et al, 2012; Feniman et al, 2008; Handžic-Cuk et al, 1996). Finally, most studies have identified no gender predilection for later increased risk for otologic disease, with a minority reporting an increased risk in males (Ahn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Younger children tend to have a higher prevalence of middle ear effusions and hearing loss than older children (Chen et al, 2012; Dhillon, 1988; Grant et al, 1988). Otologic disease is often seen as a gender-neutral issue, although some evidence suggests males require additional pressure equalization (PE) tubes (Feniman et al, 2008). Similarly, children with complete cleft palates rather than incomplete clefts require PE tubes more often following surgery and recover Eustachian tube function more slowly as they age (Handžic-Cuk et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, AC screenings were not robust in identifying conductive components because of the middle ear pathology, bone conduction (BC) testing was not explored as ambient noise levels could not be monitored without appropriate instrumentation, and tympanometry was not sensitive in identifying middle ear problems in individuals with CLP. Feniman et al (2008), reported that only 65% of infants showed middle ear problems through tympanometry, as compared with 84% through otomicroscopy. D'Mello and Kumar (2007) reported that tympanometry, with confirmation by the otolaryngologist, was successful in detecting the presence of middle ear effusion, cerumen, and chronic suppurative otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…Feniman et al had also concluded that it was difficult to get a proper tympanometry results by using single frequency probe (226 Hz) in infants below 5 months of age. 8 Multiple frequency probes have been advocated for very small infants. Therefore single frequency probe was highly unreliable in age below 6 months of age.…”
Section: Discussionmentioning
confidence: 99%